2006
DOI: 10.1111/j.1399-0012.2006.00596.x
|View full text |Cite
|
Sign up to set email alerts
|

FTY720 (fingolimod) in renal transplantation

Abstract: FTY720 (Fingolimod) is a novel immunomodulator with a mode of action that is completely different from classical immunosuppressants. FTY is a structural and functional analogue of the natural serum lipid, sphingosine, and is the first in a new class of drugs called sphingosine 1-phosphate receptor (S1P-R) modulators. This review discusses the recent findings on the mechanism of action, preclinical models and outlines the results of the ongoing clinical development program. FTY is highly effective in prolonging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(52 citation statements)
references
References 54 publications
2
49
1
Order By: Relevance
“…These effects could also be shown with the phosphorylated S1P receptor agonist AFD-R (22), suggesting that targeting S1P receptors locally in the lung and on DC was sufficient to inhibit proinflammatory cytokine release and virus-specific T cells expansion. Others have reported that systemic delivery of sphingosine analog FTY720 can sequester normal expanding lymphocytes in lymphoid organs in various models (30)(31)(32) including during virus infection (33). However, this was unlikely a mechanism in our studies for the following reasons.…”
Section: Discussioncontrasting
confidence: 42%
“…These effects could also be shown with the phosphorylated S1P receptor agonist AFD-R (22), suggesting that targeting S1P receptors locally in the lung and on DC was sufficient to inhibit proinflammatory cytokine release and virus-specific T cells expansion. Others have reported that systemic delivery of sphingosine analog FTY720 can sequester normal expanding lymphocytes in lymphoid organs in various models (30)(31)(32) including during virus infection (33). However, this was unlikely a mechanism in our studies for the following reasons.…”
Section: Discussioncontrasting
confidence: 42%
“…FTY720 has been proven to prolong allograft survival in both rodents and men (26,27) by acting as a sphingosine-1 phosphate (S1P) agonist inducing a prolonged down-regulation of the cell surface expression of the S1P receptor. The latter enables a blockade of S1P-mediated T cell egress from SLO, which is normally induced by a S1P gradient from blood and lymph fluid to tissue (28).…”
Section: Various Target Cells Such As Cd4mentioning
confidence: 99%
“…Phase I and phase II studies showed good tolerability and efficacy in preventing acute rejection in de novo transplant recipients (reviewed in reference 55 ). These studies also described the pharmacokinetics, characterized by a prolonged absorption phase, a long half-life (ϳ200 h) and a large volume of distribution, consistent with the lipophilic properties of the drug.…”
Section: Fingolimod (Fty720)mentioning
confidence: 99%